Short-term temporal analysis and children's knowledge of the composition of important medicinal plants: the structural core hypothesis - Daniel Carvalho Pires Sousa; Washington Soares Ferreira Júnior; Ulysses Paulino Albuquerque (BMC, 2022)
Abstract Background Measures of the importance of medicinal plants have long been used in ethnobotany and ethnobiology to understand the influence of social-ecological system factors in the formation of individuals' differential knowledge and use. However, there is still a gap in empirical studies that seek to understand the temporal aspects of this process. Methods To overcome this issue, we used the concept of the structural core of medicinal plants, a theoretical-evolutionary model, which argues that the importance of medicinal plant resources is related to the increase in individual and population fitness. It represents the set of the most effective and available resources that would treat the most common diseases in an environment. This composition of knowledge would be conservative over space and time. To test these questions, we hypothesized that the composition of the structural core remains constant during temporal changes in a social-ecological context, and that the composition of the infantile structural core (new generation) is similar to that of the adults (older generation). For 2 years, we tracked the structure of important medicinal plants among the same 49 residents of a community located in Vale do Catimbau in Pernambuco, Brazil. We also compared the importance of the medicinal plants among two different generations, children/adolescents and adults, in the same space/time context. Results and Conclusion Our results refuted both hypotheses. Regarding the composition of important medicinal plants through temporal variations and for children's learning, our results were not predicted by the model. This suggests that the structural core should not be regarded as a conservative phenomenon, but rather a congenital, dynamic, and plastic occurrence that has adapted to configure itself as a short-term population response to the treatment of local diseases.